2005
DOI: 10.1093/cercor/bhi022
|View full text |Cite
|
Sign up to set email alerts
|

The Metabotropic Glutamate Receptor mGluR3 is Critically Required for Hippocampal Long-term Depression and Modulates Long-term Potentiation in the Dentate Gyrus of Freely Moving Rats

Abstract: Group II metabotropic glutamate receptors (mGluRs) play an important role in the regulation of hippocampal synaptic plasticity in vivo: long-term potentiation (LTP) is inhibited and long-term depression (LTD) is enhanced by activation of these receptors. The contribution, in vivo, of the individual group II mGluR subtypes has not been characterized. We analysed the involvement of the subtype mGluR3 in LTD and LTP. Rats were implanted with electrodes to enable chronic measurement of evoked potentials from media… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(38 citation statements)
references
References 52 publications
1
37
0
Order By: Relevance
“…These results were interpreted to demonstrate that the activity of LY354740 was mediated by mGluR2. Another study (Pöschel et al, 2005) suggested that "mGluR3 is critically required for hippocampal LTP [long-term potentiation]" based on the activity of commercial NAAG in an in vivo preparation. In these studies, and others, the use of NAAG to show the role of mGluR3 needs to be re-evaluated because almost all studies have not have addressed the issue of glutamate contamination.…”
Section: Discussionmentioning
confidence: 99%
“…These results were interpreted to demonstrate that the activity of LY354740 was mediated by mGluR2. Another study (Pöschel et al, 2005) suggested that "mGluR3 is critically required for hippocampal LTP [long-term potentiation]" based on the activity of commercial NAAG in an in vivo preparation. In these studies, and others, the use of NAAG to show the role of mGluR3 needs to be re-evaluated because almost all studies have not have addressed the issue of glutamate contamination.…”
Section: Discussionmentioning
confidence: 99%
“…In field CA1, group I mGluR-dependent LTD induced by DHPG appears to be dependent on protein, but not mRNA, synthesis (and is absent in mGluR5 knock-out mice) (Huber et al, 2000(Huber et al, , 2001. At perforant path-dentate granule cell synapses, group I mGluR-LTD has also been reported to be protein synthesis dependent (Naie and Manahan-Vaughan, 2005), but LTD induced by group II or III mGluR agonists was not (Naie and Manahan-Vaughan, 2005;Pöschel and Manahan-Vaughan, 2005), although NMDA receptor-dependent LTD has yet to be examined. Interestingly, a recent study (Nosyreva and Huber, 2005) found that, although DHPG-induced LTD was protein synthesis dependent in slices from 21-d-old rats, it was not in slices from 8-to 15-d-old animals.…”
Section: Discussionmentioning
confidence: 99%
“…There are multiple experimental protocols, both stimulus and chemical, that can elicit LTD at Schaffer collateral-CA1 (Bolshakov and Siegelbaum, 1994;Gage et al, 1997;Oliet et al 1997;Palmer et al, 1997;Lee et al, 1998;Reyes-Harde et al, 1999;Santschi et al, 1999Santschi et al, , 2006 and other synapses (O'Mara et al, 1995;Domenici et al, 1998;Pöschel et al, 2005). Previous studies have shown that stimulus protocols pairing different stimulus frequencies and levels of postsynaptic depolarization can evoke Schaffer collateral LTDs that selectively require either NMDA or metabotropic glutamate receptor (mGluR) activation, but not both (Oliet et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Group II agonists can inhibit LTP at CA1 synapses and the dentate gyrus, while application of group I agonists induce LTP in the hippocampus [87]. Group II mGluR3 has been shown to play a vital role in the modulation of long-term depression in the dentate gyrus [89]. The group III agonist, L-AP4, causes significant short-term depression in the perforant path, and this depression is more pronounced in the medial perforant path than the lateral perforant path [88].…”
Section: Long-term Potentiation: Metabotropic Glutamate Receptorsmentioning
confidence: 99%